2011
DOI: 10.1024/0036-7281/a000273
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in Saanen-goats: Normal findings, reference intervals in awake goats, and the effect of general anesthesia

Abstract: Echocardiographic assessment of cardiac structures, dimensions, and mechanical function in goats is poorly documented. The goal of this study was to describe normal findings, establish normal values for two-dimensional (2DE) and M-mode (MME) echocardiography, and investigate the influence of general anaesthesia. Standardized 2DE and MME recordings were obtained on 22 healthy female Saanen goats (3.7 ± 1.1 years [mean ± SD], 60.2 ± 10.6 kg) awake (standing) and during isoflurane anesthesia (sternal recumbency).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Longitudinal and circumferential strain measurements were generally higher in anesthetized compared to awake goats, consistent with an overall increase in systolic LV performance. These findings were in agreement with previously reported findings obtained from the same population of goats, indicating that M-mode-based and 2DE-based LV ejection phase indices and peak systolic LV wall thickness were significantly higher under general anesthesia [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Longitudinal and circumferential strain measurements were generally higher in anesthetized compared to awake goats, consistent with an overall increase in systolic LV performance. These findings were in agreement with previously reported findings obtained from the same population of goats, indicating that M-mode-based and 2DE-based LV ejection phase indices and peak systolic LV wall thickness were significantly higher under general anesthesia [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, overall LV systolic performance appeared to be increased (see above). This can be attributed to the sum of interacting effects of altered loading, contractility, and heart rate caused by anesthetic drugs, fluid therapy, and mechanical ventilation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A colour-flow Doppler echocardiography performed each day before each PW-Doppler echocardioghraphic protocol did not reveal any abnormality. Particularly, any suspicion of interatrial communication or patent foramen ovale such as reported in 9 healthy Saanen goats [17] could be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Time-motion mode (M-mode), two-dimensional (2D) and colour-flow Doppler echocardiography has been demonstrated to be feasible in Philippine native goats [14] and in a pygmy goat [15]. More recently, M-mode and 2D-echocardiographic reference values have been established in awake healthy Saanen goats after repeatability and variability studies [16] and the effect of general anaesthesia in Saanen goats was studied using 2D- and colour Doppler echocardiography [17]. By contrast, no reference values of PW Doppler parameters were reported in goats.…”
Section: Introductionmentioning
confidence: 99%